2019
DOI: 10.1186/s40478-019-0759-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of ephrin-A5 aggravates disease progression in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease that affects motor neurons in the brainstem, spinal cord and motor cortex. ALS is characterized by genetic and clinical heterogeneity, suggesting the existence of genetic factors that modify the phenotypic expression of the disease. We previously identified the axonal guidance EphA4 receptor, member of the Eph-ephrin system, as an ALS disease-modifying factor. EphA4 genetic inhibition rescued the motor neuron phenotype in zebrafish and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In summary, it may be that other Eph receptors and/or EphA4 ligands could be involved in the pathophysiology of ALS. We have recently shown that a reduction of ephrin-A5 levels to 50% does not improve but accelerates disease progression in the SOD1 G93A mouse model 28 . Whether this effect is caused by inhibitory interactions in cis with EphA4 expressed at the same membrane, or by interactions with other Eph receptors, is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In summary, it may be that other Eph receptors and/or EphA4 ligands could be involved in the pathophysiology of ALS. We have recently shown that a reduction of ephrin-A5 levels to 50% does not improve but accelerates disease progression in the SOD1 G93A mouse model 28 . Whether this effect is caused by inhibitory interactions in cis with EphA4 expressed at the same membrane, or by interactions with other Eph receptors, is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Different mouse strains were obtained at the Jackson Laboratory (Ben Harbor, ME): the human mutant SOD1 overexpressing mouse (B6.SOD1 G93A ; B6.Cg-Tg(SOD1*G93A)1Gur/J; stock number 004435), an EphA4 floxed mutant mouse that has loxP sites flanking the exon 3 of the Epha4 gene (EphA4 tm1.1Bzh ; Epha4tm1.1Bzh/J; stock number 012916), the CAG-CreER TM mouse (B6.Cg-Tg(CAG-cre/Esr1*)5Amc/J; stock number 004682), and the Thy1-CreER T2 mouse (SLICK-H; Tg(Thy1-cre/ERT2,-EYFP)HGfng/PyngJ; stock number 012708). All animals were housed under standard conditions according to the guidelines of the University of Leuven (KU Leuven), with a 12h light-dark cycle and with access to food and water ad libitum as previously described 28 . Mice were maintained in a C57BL/6J genetic background, and were bred between them to obtain the experimental groups: EphA4 F/+ (EphA4 het ), CAG-CreER TM EphA4 F/+ (CAG-EphA4 het ), EphA4 F/F (EphA4), CAG-CreER TM EphA4 F/F (CAG-EphA4), Thy1-CreER T2 EphA4 F/F (Thy1-EphA4), SOD1 G93A EphA4 F/+ (SOD1-EphA4 het ), SOD1 G93A CAG-CreER TM EphA4 F/+ (SOD1-CAG-EphA4 het ), SOD1 G93A EphA4 F/F (SOD1-EphA4), SOD1 G93A CAG-CreER TM EphA4 F/F (SOD1-CAG-EphA4), SOD1 G93A Thy1-CreER T2 EphA4 F/F (SOD1-Thy1-EphA4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations